Angiotensin-converting enzyme 2 activation suppresses pulmonary vascular remodeling by inducing apoptosis through the Hippo signaling pathway in rats with pulmonary arterial hypertension. (18th August 2019) - Yan, Daole; Li, Gang; Zhang, Yaozhong; Liu, Yinglong
ABSTRACT: Objective:  To investigate the effects of angiotensin-converting enzyme 2 (ACE2) activation on pulmonary arterial cell apoptosis during pulmonary vascular remodeling associated with pulmonary arterial hypertension (PAH) and to elucidate potential mechanisms related to Hippo signaling.Methods: PAH model was developed by injecting monocrotaline combined with left pneumonectomy using Sprague-Dawley rat. Then, resorcinolnaphthalein (Res; ACE2 activator), MLN-4760 (ACE2 inhibitor), A-779 (Mas inhibitor), and 4-((5, 10-dimethyl-6-oxo-6, 10-dihydro-5H-pyrimido[5, 4-b]thieno[3, 2-e][1, 4]diazepin-2-yl)amino) benzenesulfonamide (XMU-MP-1; MST1/2 inhibitor) were administered via continuous subcutaneous or intraperitoneal injection for 3 weeks. Animals were randomly divided into six groups: control, PAH, PAH+Res, PAH+Res+MLN-4760, PAH+Res+A-779, and PAH+Res+XMU-MP-1. On 21 day, hemodynamics and pathologic lesions were evaluated. Apoptosis and apoptosis-associated proteins were detected by TUNEL and western blotting. ACE2 activity and Hippo pathway components including large tumor suppressor 1 (LATS1), Yes-associated protein (Yap), and phosphorylated Yap (p-Yap) were investigated by fluorogenic peptide assays and western blotting.Results: In the PAH models, the mean pulmonary arterial pressure, right ventricular hypertrophy index, pulmonary vascular remodeling, anti-apoptotic protein Bcl-2 and Yap were all increased but the pulmonary arterial cell apoptosis, pro-apoptotic proteins caspase-3 and Bax were lower. ACE2 activation significantly ameliorated pulmonary arterial remodeling, this action was related to increased apoptosis and up-regulation of LATS1 and p-Yap. These protective effects were mitigated by the co-administration of A779 or MLN-4760. Moreover, inhibiting the Hippo/LATS1/Yap pathway with XMU-MP-1 blocked apoptosis in pulmonary vascular cells induced by ACE2 activation during the prevention of PAH.Conclusions: Our findings suggest that ACE2 activation attenuates pulmonary vascular remodeling by inducing pulmonary arterial cell apoptosis via Hippo/Yap signaling during the development of PAH.